Modeling the Social and Epidemiological Causes of Hearing Loss - Kouilily, F.; Yousfi, N.; Achtaich, N.; El Khasmi, M. (Revista Mexicana de Ingenieria Biomedica, 2018)
Hearing loss result from genetic causes, complications at birth, certain infectious diseases, chronic ear infections, noise exposure, demographic characteristics (age, sex, race, education, and study site) and cardiovascular factors (smoking status, hypertension, diabetes and stroke). In this study, we propose a new mathematical model formulated by ordinary differential equations (ODEs) that takes into account the some causes of hearing loss. The analysis of the model is investigated. In addition, numerical simulations are presented in order to validate our theoretical results.